Occupational hazards and safety practices among staff of Port Harcourt Electricity Distribution Company - Ogolo, Belinda Nnenne; Azuonwu, Goodluck (Faculty of Natural and Applied Sciences Journal of Scientific Innovations, 2023)
This study investigated occupational hazards and safety practices among workers of the Port Harcourt Electricity Distribution Company (PHED) in the Port Harcourt metropolis of Rivers State, Nigeria. The study utilized a descriptive cross-sectional survey approach, involving a population of 1,538 employees working for PHED in the urban area of Port Harcourt. A sample size of 414 was selected using a multi-staged sampling procedure took part in the study. Data was collected using a structured questionnaire with a reliability coefficient of 0.84. The result showed that occupational hazards were experienced by the majority of the workers, with psychosocial hazards (87.9%) being the most common type of occupational hazard. The result also revealed that 73.9% of the staff experienced physical hazards resulting from their jobs. The result showed that 82.1% of the workers of the PHED suffered ergonomic hazards. The result showed that the grand mean of 3.13±0.77 is greater than the criterion mean of 2.5, which implies that good safety practices were found among the workers of the PHED. It was concluded that workers of PHED mainly experienced psychosocial hazards, though other categories of occupational such as physical hazards and ergonomic hazards were also experienced. Good safety practices were found among the workers, and this would reduce the impact of such hazards on the workers. It was recommended that PHED improve the security of their staff, particularly when they are on duty, by attaching security personnel to them to avoid psychosocial hazards like assault.